PENGARUH EKSPEKTASI USAHA, EKSPEKTASI KINERJA, EFIKASI DIRI DAN KEPERCAYAAN TERHADAP KEPUASAN KONSUMEN PADA NURUL HENNA ACEH DI BANDA ACEH - Nurul Akmal; Sorayanti Utami (Departemen Manajemen, 2022)
This study aims to determine the influence of business expectations, performance expectations, self efficacy, and trust in customer satisfaction. Empirical study was conducted at Nurul Henna Aceh in Banda Aceh City using questionnaire as research instrument, which the sample in this research is equal to 163 people. Nonprobability Sampling is used as sampling technique with Purposive Sampling method. Multiple linear method is used as data analysis method using IBM SPSS 22 software. The results of this study indicate that business expectations have a negative and significant effect on customer satisfaction, performance expectations have a positive and significant effect on customer satisfaction, self efficacy has a positive and significant effect on customer satisfaction, trust has a positive and significant impact on customer satisfaction, and besides obtained the result that there is influence simultaneously to customer satisfaction.